DEVELOPING THE ROOTS-ELT MODEL FOR TEACHING ENGLISH IN REMOTE PRIMARY SCHOOLS: A CONTEXT-RESPONSIVE FRAMEWORK FOR 3T SETTINGS IN NORTH TORAJA, INDONESIA - Roni La'biran; Resnita Dewi (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
Teaching English in remote and resource-constrained primary schools requires a model that is pedagogically simple, culturally meaningful, and resilient when digital infrastructure is limited. This conceptual development study proposes the ROOTS-ELT model for primary-school English teaching in 3T-type settings in North Toraja, Indonesia. The study used a design-oriented synthesis of recent research on teaching English to young learners, rural English education, culturally responsive pedagogy, low-resource instruction, and current Indonesian primary-school English policy. The synthesis identified five interrelated design requirements: familiar cultural content, comprehensible oral input, low-tech multimodal resources, structured peer interaction, and continuous recycling with performance-based assessment. These requirements were translated into five instructional stages represented by ROOTS: Relate to local experience, Offer comprehensible input, Organize collaborative practice, Task learners with meaningful communication, and Spiral review and assessment. The model positions Toraja culture and everyday village life as learning resources while maintaining a clear English-language objective. It treats technology as optional support rather than a prerequisite and allows strategic use of Indonesian and local languages as scaffolding. Because this article develops a conceptual framework rather than reporting a classroom intervention, the model requires empirical validation through teacher review, pilot teaching, learner performance measures, and iterative revision in selected remote primary schools in North Toraja.